Acylated oleanane-type triterpene oligoglycosides from the flower buds of Camellia sinensis var. assamica. Issue 5 (4th February 2015) - Ohta, Tomoe; Nakamura, Seikou; Nakashima, Souichi; Matsumoto, Takahiro; Ogawa, Keiko; Fujimoto, Katsuyoshi; Fukaya, Masashi; Yoshikawa, Masayuki; Matsuda, Hisashi
Abstract: Eight new acylated oleanane-type triterpene oligoglycosides, floraassamsaponins I, II, III, IV, V, VI, VII, and VIII, were isolated from the flower buds of Camellia sinensis var. assamica . The chemical structures of new constituents were characterized on the basis of chemical and physicochemical evidence. In the present study, floraassamsaponins I and II with sugar moiety at 28-position were obtained from the flower buds of C. sinensis var. assamica . In the past, acylated triterpene oligoglycosides with sugar moiety at 28-position have not been isolated from the flower buds of Camellia sinensis var. sinensis . This finding is interesting from the perspective of chemotaxonomy of Camellia plants. In addition, acylated oleanane-type triterpene saponins significantly inhibited the aggregation of Aβ42. Graphical abstract: